ADMISSIBILITY OF EVIDENCE IN THE INVESTIGATION OF ROAD TRAFFIC ACCIDENTS IN PRE-TRIAL CRIMINAL PROCEEDINGS - Labozeviča, Sanita (Administrative and Criminal Justice, 2019)
The research paper is devoted to the problems of evidence’s disposal admissibility in road accident investigation during pre-trial criminal proceedings. The understanding of evidence admissibility in the Latvian and foreign criminal procedural law theory and law enforcement practice is examined; implementation of the establishment during pre-trial criminal proceedings by investigating road accident crimes during pre-trial criminal proceedings. The objective of the research paper: to investigate theoretical and practical issues of the establishment of disposal admissibility by investigating road accident crimes during pre-trial criminal proceedings; to identify problems in this context and to offer their solutions. During the practice pre-trial criminal investigation in road accident cases indicate shortcomings in the legal framework, as well as the competence of officials conducting criminal proceedings, the organization of work and the lack of methodological materials and standardized forms related to the specific nature of the road accident investigation. The solutions proposed by the author are related to the strengthening of the attachments’ admissibility specified in section 130 of the Criminal Procedure Law as evidence in criminal proceedings.